ChemInform Abstract: Dioxomolybdenum Complexes as Excellent Catalysts for the Deoxygenation of Aryl Ketones to Aryl Alkenes. Issue 11 (February 2016) - Fernandes, Tiago A.; Fernandes, Ana C.
Abstract: The novel method is advantageous with regards to operational simplicity and use of an inexpensive, environmentally friendly air stable catalyst.